The Anxiety of Being Postcolonial: Ideology and the Contemporary Postcolonial Novel - Kanaganayakam, Chelva (Miscelánea: A Journal of English and American Studies, 2003)
This paper draws attention to the notion of "anxiety" as a significant aspect of contemporary postcolonial literature. Postcolonial authorship has become, in recent years, a far more contested area as writers locate themselves in ways that do not necessarily reflect majoritarian perspectives. The old binaries that characterized postcolonial studies are not always applicable in the present context. The marginality of authors is compounded by shifting cultural and political situations in nations that are configuring themselves in new ways. The resulting ambivalence has led to a new subgenre of postcolonial writing: a literature of anxiety. Michael Ondaatje, Romesh Gunesekera and J.M. Coetzee are among the major authors whose recent work demonstrates the preoccupations and formal strategies of this body of writing.